Clinical Features and Influencing Factors for the Prognosis of Patients With Sudden Deafness - Lin, Wei; Xiong, Gaoyun; Yan, Kailei; Yu, Wumin; Xie, Xiaoxing; Xiang, Ze; Wu, Jian; Ge, Yanping; Wang, Ying (Frontiers in Neurology, 2022)
Backgrounds Studies on risk factors influencing the prognosis of patients with sudden onset deafness are lacking. Methods From March 2018 to March 2021, 500 patients, from the Tongde Hospital in Zhejiang Province, with sudden onset deafness were enrolled. We collected clinical information from the hospital medical records, including certain demographic characteristics, information related to sudden-onset deafness, and laboratory parameters. Univariate and multivariate analyses were performed to determine independent prognostic risk factors for patients with sudden deafness. Additionally, we also employed orthogonal partial least squares discriminant analysis (OPLS-DA) to analyze the data of these enrolled patients. Results The baseline clinical characteristics of the enrolled patients were analyzed. Based on their prognoses, the included patients were divided into the overall effective and ineffective groups. Between these two groups, the univariate and multivariate analyses were performed. Age, type of hearing curve at the initial diagnosis, acute phase, and sudden deafness site were found to be independently associated with the prognoses of patients with sudden deafness (all P < 0.05). Through the OPLS-DA, the sudden deafness site was found to be an indicator with the highest predictive power. Conclusions Age, type of hearing curve at the initial diagnosis, acute phase, and sudden deafness site were all independently correlated with the prognoses of patients with sudden deafness and, therefore, need to be emphasized.